The mTOR–Autophagy Axis and the Control of Metabolism - Deleyto-Seldas, Nerea; Efeyan, Alejo (Frontiers in Cell and Developmental Biology, 2021)
The mechanistic target of rapamycin (mTOR), master regulator of cellular metabolism, exists in two distinct complexes: mTOR complex 1 and mTOR complex 2 (mTORC1 and 2). MTORC1 is a master switch for most energetically onerous processes in the cell, driving cell growth and building cellular biomass in instances of nutrient sufficiency, and conversely, allowing autophagic recycling of cellular components upon nutrient limitation. The means by which the mTOR kinase blocks autophagy include direct inhibition of the early steps of the process, and the control of the lysosomal degradative capacity of the cell by the transactivation of genes encoding structural, regulatory and catalytic factors. Upon inhibition of mTOR, autophagic recycling of cellular components result in the reactivation of mTORC1, thus autophagy lies both downstream and upstream of mTOR. The functional relationship between the mTOR pathway and autophagy involves complex regulatory loops that are significantly deciphered at the cellular level, but incompletely understood at the physiological level. Nevertheless, genetic evidence stemming from the use of engineered strains of mice have provided significant insight in the overlapping and complementary metabolic effects that physiological autophagy and the control of mTOR activity exert during fasting and nutrient overload.